1999
DOI: 10.1007/s004670050582
|View full text |Cite
|
Sign up to set email alerts
|

Serum beta 2 -microglobulin and immunoglobulin levels in young hemodialysis patients

Abstract: Amyloidosis is a complication of long-term hemodialysis treatment. The major histological feature of hemodialysis-associated amyloidosis (HAA) is the deposition of amyloid fibrils in the affected lesions, due, in part, to elevated serum beta2-microglobulin (beta2M) levels. In vitro studies reveal that serum immunoglobulin light and heavy chains co-deposit with beta2M in tissues affected by HAA. Only one study of HAA has been performed in young dialysis patients. We therefore assessed risk factors for HAA in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…B2M is the only MM studied in depth with respect to its kinetics, but its disadvantages are well known . It has a fluctuating production rate and complex rebound kinetics with high compartmentalization, elevated levels in nonrenal diseases, is affected by heparin and its production can increase during HD . Intradialytic rise in B2M was previously attributed to hemoconcentration with UF, but a true rise in intradialytic B2M production was demonstrated with higher dialyzer surface area and certain membrane types (Polymethylmethacrylate 2.0 m 2 , cuprophane and cellulose) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B2M is the only MM studied in depth with respect to its kinetics, but its disadvantages are well known . It has a fluctuating production rate and complex rebound kinetics with high compartmentalization, elevated levels in nonrenal diseases, is affected by heparin and its production can increase during HD . Intradialytic rise in B2M was previously attributed to hemoconcentration with UF, but a true rise in intradialytic B2M production was demonstrated with higher dialyzer surface area and certain membrane types (Polymethylmethacrylate 2.0 m 2 , cuprophane and cellulose) .…”
Section: Discussionmentioning
confidence: 99%
“…It has a fluctuating production rate and complex rebound kinetics with high compartmentalization, elevated levels in nonrenal diseases, is affected by heparin and its production can increase during HD . Intradialytic rise in B2M was previously attributed to hemoconcentration with UF, but a true rise in intradialytic B2M production was demonstrated with higher dialyzer surface area and certain membrane types (Polymethylmethacrylate 2.0 m 2 , cuprophane and cellulose) . Proposed mechanisms for this rise include B2M release from leukocytes due to complement activation during HD, serum osmolar changes and presence of endotoxin‐like substances in dialysate, and cell shedding during passage through the dialyser .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less information is available in the published literature on this issue in HD patients. Studies have reported lower β 2 microglobulin levels, improved nutritional markers, an increase in true dry weight, higher haemoglobin and endogenous erythropoietin levels, lower potassium and uric acid levels, better phosphate balance and improved quality of life in HD patients with better preserved RRF 12,32–40 …”
Section: Potential Mechanisms Of Benefit Of Rrf In Dialysismentioning
confidence: 99%
“…Studies have reported lower b2 microglobulin levels, improved nutritional markers, an increase in true dry weight, higher haemoglobin and endogenous erythropoietin levels, lower potassium and uric acid levels, better phosphate balance and improved quality of life in HD patients with better preserved RRF. 12,[32][33][34][35][36][37][38][39][40] Residual renal function is also an important component of the overall treatment efficacy delivered by either PD or HD, and contributes to the success of the concept of incremental dialysis whereby patients with significant RRF can be initiated on smaller doses of dialysis at the beginning, hence according such patients better quality of life and less restrictions from the full dose of dialysis right from the onset.…”
Section: Potential Mechanisms Of Benefit Of Rrf In Dialysismentioning
confidence: 99%